Time Frequency Features of Rotor Systems with Slowly Varying Mass - Tao Yu; Qingkai Han (Shock and Vibration)
With the analytic method and numerical method respectively, the asymptotic solutions and finite element model of rotor system with single slowly varying mass is obtained to investigate the time frequency features of such rotor system; furthermore, with given model of slowly varying mass, the rotor system with dual slowly varying mass is studied. For the first order approximate solution is used, there exists difference between the results with analytic method and numerical method. On the base of common characteristics of rotor system with dual slowly varying mass, the general rules and formula describing the frequency distribution of rotor system with multiple slowly varying mass are proposed.